Emerging technologies and virtual medicine in obesity management - Van Zyl, F H; Noeth, M; Diab, P N; Conradie-Smit, M; May, W (South African medical journal, 2025)
RECOMMENDATIONS 1. Implementation of strategies in the management of obesity can be delivered through web-based platforms (e.g. online education on medical nutrition therapy and physical activity) or mobile devices (e.g. daily weight reporting through a smartphone phone application) (Level 2a, Grade B). 2. We suggest that healthcare providers incorporate individualised feedback and follow-up (e.g. personalised coaching or feedback via phone or email) into technology-based management strategies to improve weight loss outcomes (Level 4, Grade D). 3. The use of wearable activity-tracking technology should be part of a comprehensive strategy for weight loss (Level 1a, Grade A).